Lewis Acid Behavior of SF4: Synthesis, Characterization, and Computational Study of Adducts of SF4 with Pyridine and Pyridine Derivatives. Issue 16 (6th March 2015) - Chaudhary, Praveen; Goettel, James T.; Mercier, Hélène P. A.; Sowlati‐Hashjin, Shahin; Hazendonk, Paul; Gerken, Michael
Abstract Sulfur tetrafluoride was shown to act as a Lewis acid towards organic nitrogen bases, such as pyridine, 2, 6‐dimethylpyridine, 4‐methylpyridine, and 4‐dimethylaminopyridine. The SF4⋅NC5H5, SF4⋅2, 6‐NC5H3(CH3)2, SF4⋅4‐NC5H4(CH3), and SF4⋅4‐NC5H4N(CH3)2 adducts can be isolated as solids that are stable below −45 °C. The Lewis acid–base adducts were characterized by low‐temperature Raman spectroscopy and the vibrational bands were fully assigned with the aid of density functional theory (DFT) calculations. The electronic structures obtained from the DFT calculations were analyzed by the quantum theory of atoms in molecules (QTAIM). The crystal structures of SF4⋅NC5H5, SF4⋅4‐NC5H4(CH3), and SF4⋅4‐NC5H4N(CH3)2 revealed weak SN dative bonds with nitrogen coordinating in the equatorial position of SF4. Based on the QTAIM analysis, the non‐bonded valence shell charge concentration on sulfur, which represents the lone pair, is only slightly distorted by the weak dative SN bond. No evidence for adducts between quinoline or isoquinoline with SF4 was found by low‐temperature Raman spectroscopy.